Brazilian version of the Diabetic Foot Self-Care Questionnaire of the University of Malaga, Spain: cross-cultural adaptation - Amelina de Brito Belchior; Rhanna Emanuela Fontenele Lima de Carvalho; Florência Gamileira Nascimento; Carla Cristina de Sordi; Raquel Rodrigues da Costa Brilhante; Thereza Maria Magalhães Moreira; Sherida Karanini Paz de Oliveira (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To carry out the cross-cultural adaptation of the Diabetic foot self-care questionnaire of the University of Malaga, Spain for Brazil. Method: Methodological study carried out in six stages: initial translation; synthesis of the translations; backtranslation or back-translation; review by a committee of experts; pre-testing and submission of the documents to the authors of the instrument, in August/2020 to January/2021. The Content Validity Index was calculated to assess the objectivity of the content validity. Kappa and Exact Binomial Distribution Test, indicated for small samples, were used to assess the reliability of agreement between the experts. Results: The ten experts selected, obtained an average score of 8.1 ± 3.0 confirming their high degree of expertise and competence. In terms of semantic, idiomatic, cultural, and conceptual equivalence, the items had a CVI ≥0.90. The pre-test was carried out with 32 people with diabetes and only one found it very difficult, demonstrating that the target audience was able to understand the instrument. Conclusion: The Diabetic foot self-care questionnaire of the University of Malaga - Brazilian version is a valid tool for assessing foot self-care behavior in people with diabetes, as well as being understandable, easy, and quick for patients to complete.